2020
DOI: 10.33495/jacr_v8i9.20.139
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of improvement perimeters in preventing and combating soil erosion

Abstract: Work conducted over the course of a year have had as primary purpose the effect of ecological reconstruction through afforestation and other works (support fences, cross and longitudinal works în ravinees) in improvement perimeters Diviciori 1 (compartment 73) and Diviciori 3 (compartment 49). Forest vegetation was installed 30 years ago in 73, according to afforestation formula 7PiN-2Pa (Fr) -1 seadbucktorn and 50 years in 49, according to the afforestation formula: 5PiN-2Pi-3Mo. Stands were led using silvote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In the semi-arid environment of the Mediterranean area, they found that the effect of spatially-structured vegetation on runoff and sediment production was very dynamic and depends on the intensity of precipitation and the slope of the terrain. With the amount and intensity of rainfall above certain thresholds [57], the effect of vegetation on surface runoff and erosion can be weakened [58,59]. Nainar et al [60] found that in plots with litter, surface runoff increased linearly with precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…In the semi-arid environment of the Mediterranean area, they found that the effect of spatially-structured vegetation on runoff and sediment production was very dynamic and depends on the intensity of precipitation and the slope of the terrain. With the amount and intensity of rainfall above certain thresholds [57], the effect of vegetation on surface runoff and erosion can be weakened [58,59]. Nainar et al [60] found that in plots with litter, surface runoff increased linearly with precipitation.…”
Section: Discussionmentioning
confidence: 99%